The Effect of Entrepreneurial Orientation on International Performance of SMES in Bandung City with Business Model Innovation as a Mediating Variable - Yudhya Muchlizardy (Green Publisher Indonesia, 2026)
MSMEs have a strategic role in the national economy, especially in creating jobs and encouraging economic growth. However, many MSMEs in the City of Bandung face challenges in improving their international performance. This study aims to analyze the influence of Entrepreneurial Orientation (EO) on International Performance (IP) with Business Model Innovation (BMI) as a mediating variable in MSMEs. The research method used is a quantitative approach with the Partial Least Squares (PLS) analysis technique. Data were collected through a survey of MSME actors in the City of Bandung. The results of the study show that EO has a positive effect on BMI and IP. In addition, BMI is proven to be a significant mediating variable in the relationship between EO and IP. These findings indicate that innovation in business models is a key factor in increasing the competitiveness of MSMEs in the international market. Therefore, MSME actors are advised to strengthen their entrepreneurial orientation and continue to innovate in business models in order to compete globally.